The effect of Teaching Games for Understanding learning models on improving learning outcomes in Physical Education - Allif Reza Fauzi; Fajar Ari Widiyatmoko; Maftukin Hudah (Universitas Sriwijaya, 2026)
Research Problems: Learning outcomes in Physical Education, Sports, and Health (PESH) among elementary school students remain relatively low, particularly in game understanding (cognitive domain) and motor skills. One instructional model that has the potential to improve these learning outcomes is the Teaching Games for Understanding (TGfU) model implemented through the Zone Game approach. Research Objectives: This study aimed to examine the effect of the Teaching Games for Understanding (TGfU) learning model implemented through the Zone Game approach on the Physical Education, Sports, and Health (PESH) learning outcomes of students at SD Negeri 02 Ngasem. Methods: This study employed an experimental method using a pretest–posttest control group design. The sample consisted of 20 students, including 11 fifth-grade students assigned to the experimental group and 9 sixth-grade students assigned to the control group, comprising 14 boys and 6 girls. Data were collected using a cognitive test consisting of multiple-choice questions and motor skill tests assessing basketball passing and dribbling, as well as soccer kicking and dribbling skills. Both assessments were administered during the pretest and posttest. Data were analyzed using tests of normality and homogeneity, followed by paired-samples t-tests and independent-samples t-tests. Results: The findings revealed that students in the TGfU group demonstrated significant improvements in both cognitive and motor learning outcomes based on the paired-samples t-test (p < .05). The independent-samples t-test indicated a significant difference between the experimental and control groups in motor skill outcomes (p = .010). However, no significant difference was found in cognitive learning outcomes between the two groups (p = .310). Conclusion: The Teaching Games for Understanding (TGfU) learning model implemented through the Zone Game approach was effective in improving Physical Education, Sports, and Health (PESH) learning outcomes, particularly students' motor skills. However, compared with conventional instruction, the model did not demonstrate a significant advantage in improving students' cognitive learning outcomes.